KUALITAS PELAYANAN PADA BADAN KESATUAN BANGSA DAN POLITIK KOTA BEKASI - Alya Dwi Rahayu; Hanny Purnamasari (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2023)
There is often a difference between the two in terms of service quality, which is directly related to how well an organization serves its customers. Due to several deficiencies, the public services provided by the government in this case are not in accordance with the standards set. Service indicators are still more conceptual in nature, and their implementation is still far from expectations, such as Law 25 of 2009 concerning Public Services which has not been fully implemented. This study aims to describe and analyze the data collected in explaining the quality of service at the Bekasi City Kesbangpol Agency, so the researchers used a qualitative descriptive approach. Researchers collect data through interviews, observation and documentation. Primary and secondary data are used in this study. Informants for in-depth interviews with related organizations and people, including the Head of Domestic Politics of the Bekasi City Kesbangpol Agency, Head of Political Education and Democracy Enhancing Sub-Division of the Bekasi City Kesbangpol Agency, and the public who carry out services at the Bekasi City Kesbangpol Agency. Reducing data, presenting data, and verifying or drawing conclusions are all necessary steps in data analysis. The findings of the study show that the Bekasi City Kesbangpol Agency is not able to provide generally satisfactory services. As required by the principle of public service in Article 4 of Law no. 25 of 2009, the Bekasi City Kesbangpol Agency has not pursued indicators such as professionalism, openness, timeliness, provision of facilities and special treatment for vulnerable groups. Keywords: Bekasi City Kesbangpol Agency, Service Quality, Public Service.